The Microporosity of Activated Carbon Fibre KF1500 Assessed by Combined CO Adsorption and Calorimetry Techniques and by Immersion Calorimetry - A. Guillot; F. Stoeckli; Y. Bauguil (Adsorption Science & Technology)
The microporous structure of the activated carbon fibre KF1500 was investigated by applying a new technique as presented here. This was based on a combination of high-pressure CO 2 adsorption measurements between 253 K and 353 K with direct measurement of the differential heats of adsorption at 298 K at low and medium coverages. The validity of this approach was tested by using two activated carbons which has been characterized previously by a variety of techniques, including immersion calorimetry. It appears that a combination of high-pressure adsorption and calorimetry with CO 2 alone is a useful tool for the characterization of the whole range of microporosity. This approach confirms earlier observations, according to which the initial stage of adsorption by strongly activated carbons corresponds to adsorption on the walls of large micropores rather than to the primary filling of small micropores.